(untitled) (Research, Society and Development, 2019)
The present text is part of a research that aimed to analyze the importance of the process of establishment of the Center of Training and Updating Center of Professionals from Basic Education Professionals (CEFAPRO), in the city of Cuiabá, state of Mato Grosso (MT), The starting point will be the assumptions of the Describing Method, since we will observe, record, analyze, describe and link facts, regarding the contribution of Cefapros to the training of education professionals in the state of MT, and, therefore, the learning process. The research was built on a qualitative approach, based on the empirical experiences of the subjects regarding the continuous training offered by Cefapro. The instruments of analysis were the interview and official documents from the Secretariat of Education-Seduc. The results indicate that: all the subjects surveyed have already participated in continuous training offered by Cefapro; the training received contributed and continues to contribute to the pedagogical practice. Another evidence is that, in this model of Continuing Education, Mato Grosso state is a pioneer. Thus, in triangulating the data with the results of the research, based on Cefapro´s reports and Seduc official documents, we realized that, despite the problems described by the respondents, Cefapro-MT is fulfilling its function: to manage continuing education and to contribute with the improvement of the pedagogical practice, from the perspective of student learning.